2007
DOI: 10.1523/jneurosci.3589-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Medial Prefrontal Cortex Is Involved in Spatial Memory Retrieval under Partial-Cue Conditions

Abstract: Brain circuits involved in pattern completion, or retrieval of memory from fragmented cues, were investigated. Using different versions of the Morris water maze, we explored the roles of the CA3 subregion of the hippocampus and the medial prefrontal cortex (mPFC) in spatial memory retrieval under various conditions. In a hidden platform task, both CA3 and mPFC lesions disrupted memory retrieval under partial-cue, but not under full-cue, conditions. For a delayed matching-to-place task, CA3 lesions produced a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 51 publications
3
68
1
3
Order By: Relevance
“…In the absence of SAH, rats with selective mPFC lesions were subjected to a MWM test similar to that used in this study and no deficits were observed [38]. Others have reported selective mPFC lesions can alter MWM performance when spatial cues are minimized or task demands are changed, which indicates an interaction between hippocampal and mPFC function in MWM performance [39,40]. Because our lesions were not selective, further speculation regarding the neuroanatomical substrate for the cognitive deficits in each model is necessarily limited, but consistent with histologic damage to these structures.…”
Section: Discussionmentioning
confidence: 76%
“…In the absence of SAH, rats with selective mPFC lesions were subjected to a MWM test similar to that used in this study and no deficits were observed [38]. Others have reported selective mPFC lesions can alter MWM performance when spatial cues are minimized or task demands are changed, which indicates an interaction between hippocampal and mPFC function in MWM performance [39,40]. Because our lesions were not selective, further speculation regarding the neuroanatomical substrate for the cognitive deficits in each model is necessarily limited, but consistent with histologic damage to these structures.…”
Section: Discussionmentioning
confidence: 76%
“…This view expands the role of the mPFC to context-sensitive learning and memory systems in general rather than fear inhibition in particular. Such a role is supported by various behavioral paradigms testing other forms of context-sensitive learning and memory (36)(37)(38)(39). This more general role for the mPFC in contextual processing is also parsimonious with its role in remote long-term contextual fear memories (10,11) and the idea that the mPFC and hippocampus are continuously in communication to allow for the systems consolidation of contextual memories as they move from a recent to remote state (15,40).…”
Section: Discussionmentioning
confidence: 94%
“…More generally, treatment of experimental animals with glutamate receptor antagonists impairs performance in a variety of cognitive tasks (Ahlander et al, 1999;Hauber and Schmidt, 1989;Karasawa et al, 2008;Venable and Kelly, 1990), whereas endogenous or exogenous glutamate receptor agonists promote cognitive performance (Clem et al, 2008;Lynch et al, 2008;Singer et al, 2010). Although definitive confirmation will require further experimentation and additional brain areas may well be involved (Jo et al, 2007), the present findings suggest that the cognitive impairment caused by elevated KYNA was likely related to reductions in extracellular glutamate in the hippocampus, and that the cognition-enhancing effects of ESBA were the result of elevated extracellular glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no data are currently available on the effects of raised KYNA levels on an animal's performance in the Morris water maze (MWM), a classic spatial learning and memory task involving the hippocampus and associated brain regions (Morris, 1984;Jo et al, 2007). The present study was designed to fill this void using experimental rats.…”
Section: Introductionmentioning
confidence: 99%